The evolution and functional morphology of hemipteran vibrational organs - Davranoglou, LR (2019)
Acoustic and vibrational signals are among the prevalent modes of arthropod communication, exploited by at least 230,000 species (Cocroft and Rodríguez, 2005). Vibroacoustic signals dominate hemipteran communication, being generated by stridulation, wing buzzing, percussion, membrane buckling and shaking of the body relative to the legs (tremulation). The last two mechanisms are produced by basi-abdominal organs known as tymbals in Cicadomorpha and tergal plates in Heteroptera, respectively, whose systematic distribution and homologies are poorly understood. Other groups, such as the planthoppers (Fulgoromorpha) and moss bugs (Coleorrhyncha), are more enigmatic, as they generate vibrations with mechanisms which have so far remained unexplored. In spite of limited available morphological evidence, it has been suggested that all hemipteran basi-abdominal organs are homologous and evolved once (Tymbalia hypothesis) (Wessel et al, 2014). The aim of this dissertation is to elucidate the evolution of hemipteran vibroacoustic organs by describing their biomechanics, morphology and systematic distribution, and to use the resulting data to test the claims of the Tymbalia hypothesis.